ANALYSIS OF ACTIVE COMPOUNDS IN BLOOD PLASMA OF MICE AFTER INHALATION OF CAJUPUT ESSENTIAL OIL (MELALEUCA LEUCADENDRON L.) - Muchtaridi Muchtaridi; Ami Tjiraresmi; Riska Febriyanti (Indonesian Journal of Pharmacy, 2015)
The research is intended for the determination of volatile compounds of cajuput oil (Melaleuca leucadendron L.) in a group of mice (3 mice) after inhaling 1 mL cajuput oil for 1/2, 1 and 2 hour(s). The blood plasma of three mice was collected in heparin tube, and the volatile compounds were isolated and concentrated using C-18 Solid Phase Extraction (SPE) column with methanol and bidistilled water mixture (60:40) as the solvent. The analysis was carried out by GC/MS. The results showed that there were 52 compounds in the cajuput oil, especially 1,8-cineole,a-terpineol, b-pinene, a-pinene, b-myrcene, 4-terpineol, linalool, g-terpinene, and terpinolene. The major compound identified in blood plasma of mice was 1,8-cineole. Half an hour after 1 mL inhalation of cajuput oil per mouse, the concentration of 1,8-cineole identified was 41.5 mg/mL, while 1 and 2 hours after 1 mL inhalation of cajuput oil, the level of 1,8-cineole in blood plasma of 3 mice was 646.9 mg/mL and 138.0 mg/mL in blood plasma of each mouse. Other compounds identified were a-terpineol, 4-terpineol linalool, terpenyl acetate and hydrocarbon terpenes. Concentrations of target compounds in the blood plasma were relatively in low level (mg/mL). In conclusion, the volatile compounds of 4-terpineol, linalool, a-terpineol and 1,8-cineol that identified in blood plasma of mice after inhalation of the cajuput oils might correlate with depressive characteristics of essential oil given by inhalation.Keywords: Cajuput, Essential Oils, Inhalation, SPE, GC-MS